PENENTUAN RUMUS BILANGAN REPRODUKSI DASAR PADA MODEL MATEMATIKA COVID-19 DARI MODEL SIR YANG DIMODIFIKASI - Anna Angela Sitinjak (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
The spread of COVID-19 has occurred and is unsettling many countries, not only the number of patients is increasing but also the economy is disrupted. Mathematical models can be used to assist in making decisions by describing both exposed and infected conditions. From the mathematical model, especially infectious diseases, the basic reproduction number can be seen. Therefore, this study aims to find the basic reproduction number of the mathematical model COVID-19 modified with various approaches using parameters close to daily life. The basic reproduction number, R0, will be free from disease if R0 <1 and endemic if R0> 1. The method used is modifying the Mathematical Model SIR to become the Mathematical Model COVID-19 by considering the isolation that is currently done to reduce the spread of COVID-19, then looking for the disease-free equilibrium point and analyzed its stability by determining the eigenvalues ​​of the Jacobian matrix. From the eigenvalues, the study result is obtained, namely Basic Reproduction Number, .